The occurrence and distribution of two mangrove-associated bivalves, Anodontia edentula (Linne) and Austriella corrugata (Deshayes) in Sapian Bay, Capiz. - Facelo, Bethea Longno (1999.)
Interest in the study of the distribution and occurrence of bivalves exists in many countries. However, little is known of mangrove bivalves especially those few species which appear to be endemic components of the mangrove forest., The two mangrove associated bivalves, Anodontia edentula Linne) and Austriella corrugata (Deshayes) are among the most common bivalves found to occur in Sapi-an bay, Capiz. The use of quadrats revealed that the species A.edentula (Linne) dominated the area. Its distribution, orientation and zonation within the mangrove clearly establish it as well adapted to the type of environment. The type of distribution pattern was known using Morisita's index showed that both species had a clumped type of distribution pattern.
Thesis (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines in the Visayas, Iloilo City.
Keywords: Mangroves -- Sapi-an Bay, Capiz; Anodontia Edentula; Austriella Corrugata